A latent class analysis of the co-occurrence of sexual violence, substance use, and mental health in youth. (15th October 2019) - Nelon, Jordan L.; De Pedro, Kris T.; Gilreath, Tamika D.; Patterson, Megan S.; Holden, Caitlin B.; Esquivel, Christi H.
Abstract: Purpose: The purpose of this study was to understand co-occurrence of sexual violence, substance use, and mental health in youth and see if there are differences in experiences among sexual identities, races, and genders. Methods: The 2017 Youth Risk Behavior Survey sampled 14, 638 high school students. Latent class analysis was used to understand the relationship between incidence of sexual violence, substance use, and depression and suicidality in a nationally representative sample. The model controlled for demographic and bullying covariates. Results: A four-class solution provided optimal fit. Classes were low risk (51.8%); low violence, frequent substance use, and high depression and suicidal ideation (29.7%); experienced violence and moderate mental health issues(5.1%); and some violence, high substance use, and high depression and suicidal ideation (13.4%). Youth who identified as sexual minority youth were almost 2.5–5 times more likely to be in the three higher risk classes than their heterosexual peers. Those who identified as "I don't know" were almost 3 times more likely to be in the three higher risk classes than heterosexual youth. Multiracial youth had higher likelihood of being in the three riskier classes compared to Caucasian youth. Females were 2.5 and 3 times more likely to be in the low violence and some violence classes compared to males. Conclusion: The study's finding distinct classes of co-occurring behavioral and mental health outcomes fill gaps in the current literature and informs practitioners that LGB youth and bi/multiracial youth were at an elevated risk of co-occurring victimization, substance use, and mental health problems.